2007
DOI: 10.1021/ja072678l
|View full text |Cite
|
Sign up to set email alerts
|

Benzimidazole and Related Ligands for Cu-Catalyzed Azide−Alkyne Cycloaddition

Abstract: Tris(2-benzimidazolylmethyl)amines have been found to be superior accelerating ligands for the copper(I)-catalyzed azide-alkyne cycloaddition reaction. Candidates bearing different benzimidazole N-substituents as well as benzothiazole and pyridyl ligand arms were evaluated by absolute rate measurements under relatively dilute conditions by aliquot quenching kinetics and by relative rate measurements under concentrated conditions by reaction calorimetry. Benzimidazole-based ligands with pendant alkylcarboxylate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
259
1
5

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 373 publications
(271 citation statements)
references
References 45 publications
6
259
1
5
Order By: Relevance
“…1) [31]. In a latter study, however, Fokin and Finn also pointed out the possibility that two Cu centers were involved in the transition state of the cycle [32], for which the following detailed kinetic studies confirmed the possibility of a σ,π-bimetallic Cu(I) intermediate [26,50,56]. Subsequent DFT calculations, carried out in the same group [22b,57], supported this hypothesis by showing that the complexation of the alkyne unit by a second metal center (bottom of Fig.…”
Section: Introductionmentioning
confidence: 91%
“…1) [31]. In a latter study, however, Fokin and Finn also pointed out the possibility that two Cu centers were involved in the transition state of the cycle [32], for which the following detailed kinetic studies confirmed the possibility of a σ,π-bimetallic Cu(I) intermediate [26,50,56]. Subsequent DFT calculations, carried out in the same group [22b,57], supported this hypothesis by showing that the complexation of the alkyne unit by a second metal center (bottom of Fig.…”
Section: Introductionmentioning
confidence: 91%
“…In contrast to the structural hypothesis by Sharpless and Fokin, [52] to be involved. [55] In their subsequent mechanistic report, [20] Fokin and Finn kinetically investigated the reaction of phenylacetylene (1 mM; 10 -50 mM) with benzyl azide…”
Section: Catalysts For Cuaac Reactionsmentioning
confidence: 99%
“…[31][32] Fokin and Finn suggest that more than one mechanism might be operational under the conditions studied and stress that the first order rate dependence in the presence of TBTA is an exception, as a second order dependence was found for most other ligand systems. [20,55] Although many questions remain unanswered, the authors conclude that the main advantage of TBTA is to "keep the metal coordination chemistry 'cleaner' by providing a high local concentration of weakly binding arms, while at the same time allowing access to open coordination sites". [20] Closely related to the tris(triazolylmethyl) amine ligands are the tris(pyridylmethyl) amines, tris(benzothiazolylmethyl) amines and tris(2-benzimidazolylmethyl) amines as well as hybrids of the latter.…”
Section: Catalysts For Cuaac Reactionsmentioning
confidence: 99%
“…In the past few years, several other polydentate aza-ligand frameworks have also been found to aid CuAAC reactions. [14][15][16][17][18][19] We recently found that TBTA also accelerates CuA C H T U N G T R E N N U N G (OAc) 2 -mediated AAC reactions that involve nonchelating azides. [9] In a number of reactions that proceed sluggishly under Cu-A C H T U N G T R E N N U N G (OAc) 2 -mediated conditions, yields of over 90 % were achieved in the presence of TBTA within 1 or 2 h. In this work, we investigated the acceleratory effects of other polytriazoles in CuA C H T U N G T R E N N U N G (OAc) 2 -mediated AAC reactions.…”
Section: Introductionmentioning
confidence: 99%